Foreign Tv Programmes In Ghana: A Comparative Study Of GTV, Viasat 1 And ETV- Ghana - Adjei, O.A. (University of Ghana, 2016)
Research evidence suggests that developed countries, particularly the US, are imperialistic when it comes to cultural products. This has been attributed to the fact that foreign television programmes, from information rich countries, flood the schedules of local television stations of information poor countries. This phenomenon is referred to as cultural imperialism. The main objective of this study was to ascertain whether the claim that there is Western dominance of media content on African media platforms was empirically founded with respect to TV programmes. Also, the study sought to find out whether media ownership and the quest to gain a market share are major determinants of the choice of content for TV stations in Ghana. A mixed methods approach was used for the study. Programme guides from GTV, Viasat 1 and ETV- Ghana were content analysed. In-depth interviews were also conducted. The combined goal of this research design was to ascertain whether media ownership affected TV programme choice. Findings of the study revealed that out of the 202 programmes analysed, GTV had the largest number of programmes, and provided more variety to its viewers. Programmes among all the stations were found to have been dominated by entertainment related content like TV Series, Drama and Musical shows. This was to the detriment of informational programmes like documentaries, political discussion, and business related shows. This bias towards entertainment related programmes though reflective of the commercial focus of the TV stations tended to exclude programmes that could contribute to the promotion of indigenous cultures and arts. Nevertheless, the expectation that programmes would be preponderantly foreign, particularly from US was not supported by an aggregation of the contents of GTV, Viasat 1 and ETV- Ghana
Thesis (MA)
Keywords: Foreign Tv Programmes; GTV; Viasat 1; ETV- Ghana; Television